A model to estimate aquaculture carrying capacity in three areas of the Philippines - Legović, Tarzan; Palerud, Rune; Christensen, Guttorm; White, Patrick; Regpala, Regie (Science Diliman: A Journal of Pure and Applied Sciences, 2009)
A model was developed to estimate the production carrying capacity of water bodies based on nutrient inputs from aquaculture and other sources, flushing rates, and the risk of algal blooms for three different areas of the Philippines – Bolinao (marine site), Dagupan (brackishwater site) and Taal Lake (freshwater site). The results suggest that aquaculture production in the Taal Lake was greater than the sustainable carrying capacity. Aquaculture structures in Bolinao were close to carrying capacity during average tidal exchange but greater than the carrying capacity during low tidal exchange and no winds. Aquaculture production in the Dagupan estuary has not overcome its carrying capacity even during low flow. However, during very low flow and no tidal flushing, carrying capacity has been overcome.